Otoritas Khalifah Utsman Dalam Pengumpulan Al-Qur'an - Anugrah Bangsawan; Masruchin Masruchin; Beko Hendro (Institut Agama Islam Sumatera Barat, 2024)
This research reveals that the authority of Utsman bin Affan caliphate played an important role in the collection of Al-Qur'an verses. For this reason, the aim of this research is to describe the steps that Utsman went through to make the Ottoman Mushaf an official mushaf. Through qualitative research methods with library research, historical approaches and critical analytical methods, several significant results have been found. The results obtained in this research are that during the leadership of Caliph Utsman bin Affan, he borrowed a Mushaf from the time of Abu Bakr, assigned the team to immediately compile the Ottoman Mushaf, then sent copies to various cities, sent the Mushaf of friends other than the Ottoman, and sent readers of Al-Qur'an equipped with mushaf. These steps reflected Uthman's proactive policy of preserving the integrity of the Qur'an and ensuring that Islamic teachings derived from Divine revelation remained unchanged and uniform throughout the Muslim community.